The Influence of Organizational Culture and Work Environment on the Employees Performance of PT Pos Indonesia (Persero) Kantor Pos Semarang 50000 - Ahmad Faishal Khairullah; Suryadi - Poerbo; Suwardi - Suwardi (Politeknik Negeri Semarang, 2020)
This study aimed to know the influenceof organizational culture on employees work performance of PT Pos Indonesia (Persero) Kantor Pos Semarang 50000, the influence of environment on employees performance of PT Pos Indonesia (Persero) Kantor Pos Semarang 50000, and the influence of organizational culture and work environment on employees performance of PT Pos Indonesia (Persero) Kantor Pos Semarang 50000.The method that used for data collection in this study wereobservation, questionnaires, and literature review. The scale that used in the questionnaires is agree disagree scale with 10 scale points. The sample that used in this study were 60 employeesof PT Pos Indonesia (Persero) Kantor Pos Semarang 50000 that choosen using incidental sampling technique. Used multiple linear regression technique for analyzing the data, it indicated that organizational culture and work environment hada positive and significant effect to employee performance. Organizational culture and work environment have 39,6% contribution to employee performance, that means every 39,6% of employee performance was explained by organizational culture and work environment, while 60,4% was explained by other factors which were not observed in this study